2022
DOI: 10.3233/jpd-213062
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration of the Globus Pallidus Internus as a Neural Correlate to Dopa-Response in Freezing of Gait

Abstract: Background: Background: Parkinson’s disease (PD) patients who develop freezing of gait (FOG) have reduced mobility and independence. While some patients experience improvement in their FOG symptoms with dopaminergic therapies, a subset of patients have little to no response. To date, it is unknown what changes in brain structure underlie dopa-response and whether this can be measured using neuroimaging approaches. Objective: We tested the hypothesis that structural integrity of brain regions (subthalamic nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…Notably, the current study showed alterations mainly in the right hemisphere of PD-FOG patients, which is consistent with a growing body of literature demonstrating that the right hemisphere appears to be selectively affected in FOG ( Fling et al, 2013 ; Peterson et al, 2014 ; Bharti et al, 2020 ; Lv et al, 2021 ; Song et al, 2021 ; Lench et al, 2022 ). The laterality of imaging abnormalities in PD-FOG patients is likely related to the fact that the right hemisphere plays a strong role in visuospatial function in right-handed subjects ( Joseph, 1988 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, the current study showed alterations mainly in the right hemisphere of PD-FOG patients, which is consistent with a growing body of literature demonstrating that the right hemisphere appears to be selectively affected in FOG ( Fling et al, 2013 ; Peterson et al, 2014 ; Bharti et al, 2020 ; Lv et al, 2021 ; Song et al, 2021 ; Lench et al, 2022 ). The laterality of imaging abnormalities in PD-FOG patients is likely related to the fact that the right hemisphere plays a strong role in visuospatial function in right-handed subjects ( Joseph, 1988 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous study also observed higher MD and RD values in the globus pallidus in PD patients of the postural instability and gait difficulties (PIGD) subtype compared to controls, and the MD value in the globus pallidus showed a positive correlation with motor severity in the PIGD group ( Nagae et al, 2016 ), in consistency with our finding. Recently, Lench et al (2022) using diffusion kurtosis imaging approach observed that PD patients with dopa-resistant FOG had higher RD value for the right GPi compared to those with dopa-responsive FOG, further supporting the link between GPi microstructure change and FOG in PD. In conclusion, the MD and RD changes in the right GPi may contribute to FOG in PD and may serve as an imaging biomarker of PD-FOG.…”
Section: Discussionmentioning
confidence: 85%
“…Recent studies have showed that diffusion changes in the globus pallidus are associated with FOG. 39,40 Within the landscape of susceptibility MRI studies in PD investigating the relationship between susceptibility and gait, our study aligns with another study demonstrating susceptibility changes in the putamen and globus pallidus. 10 Our study complements these susceptibility and diffusion MRI studies by showing that susceptibility changes in the globus pallidus are also implicated in FOG.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have showed that diffusion changes in the globus pallidus are associated with FOG. 39,40…”
Section: Discussionmentioning
confidence: 99%